"We Want Your Nurses!": Negotiating Labor Agreements in Recruiting Filipino Nurses. Issue 3 (31st August 2020) - Cabanda, Exequiel
Abstract : Nurse migration is a significant global issue that necessitates the cooperation of host and sending states. Cooperation enables countries to collaborate on shared solutions to confront global nurse imbalance that threatens health systems. While cooperation allows countries to collaborate, some states are cautious to cooperate while others participate actively. This article examines the bilateral labor negotiations between the Philippines and the following host countries: Canadian provinces—Saskatchewan (2006), Manitoba and Alberta (2006–2008), and South Australia (2008–2009) to demonstrate how bilateral parties negotiate agreements in hiring Filipino nurses. Drawing from negotiation analysis, it argues that bilateral negotiations that fulfill two necessary conditions‐ (i) participation of nonpartisan technical expert and (ii) history of previous interactions—facilitate successful negotiations that ultimately lead to labor cooperation. This article concludes by explaining how negotiation analysis uncovers the advantage of labor‐sending countries like the Philippines in successfully securing agreements that promote labor export to achieve economic growth. Abstract : "我们需要你们的护士！": 关于雇佣菲律宾籍护士的劳资协议谈判: 护士迁徙是一个重要的全球性议题, 东道国和派遣国的共同合作是促成护士迁徙的必要条件。国家间的合作有助于解决共同的问题, 从而更好地应对威胁卫生系统的全球性护士失衡。对于国家间的合作, 一部分国家持谨慎态度, 另一部分国家则更愿意积极地参与。本文研究了菲律宾与以下东道国之间的双边劳资谈判: 加拿大三大省‐萨斯喀彻温省（2006年）, 曼尼托巴省和艾伯塔省（2006‐2008年）以及南澳大利亚州（2008‐2009年）, 以展示双边各方如何就聘用菲律宾籍护士进行协商谈判。基于谈判分析, （1）无党派技术专家的参与和（2）过往共同合作的经历, 是促成双边谈判并最终实现劳资合作的两个必要条件。本文最后解释了谈判分析是如何揭示菲律宾等劳务派遣国在成功达成促进劳动力输出以实现其经济增长协议方面的优势。 Abstract : "¡Queremos a sus enfermeras!": Negociación de acuerdos laborales para contratar enfermeras filipinas: La migración de enfermeras es un problema global relevante que requiere de la cooperación entre los estados de origen y de acogida. La cooperación permite a los países colaborar en soluciones compartidas para hacer frente al desequilibrio mundial en cuanto a la disponibilidad de enfermeras que afecta a los sistemas sanitarios. Si bien la cooperación permite que los países colaboren, algunos estados son cautelosos a la hora de cooperar mientras que otros participan activamente. Este artículo examina las negociaciones laborales bilaterales entre Filipinas y los países anfitriones de Canadá y Australia – las provincias Saskatchewan (2006), Manitoba y Alberta (2006‐2008), y Australia Meridional (2008‐2009) ‐ para demostrar cómo las partes negocian acuerdos bilaterales para contratar a enfermeras filipinas. A partir del análisis de la negociación, el artículo sugiere que las negociaciones bilaterales que cumplen con dos condiciones necesarias ‐ (i) participación de un experto técnico independiente y (ii) historial de intercambios previos ‐ facilitan negociaciones exitosas que permiten llegar a una cooperación laboral. El artículo concluye explicando cómo el análisis de la negociación revela la ventaja de los países emisores de mano de obra como Filipinas para lograr acuerdos que promuevan la exportación de mano de obra y el crecimiento económico.